Research on the Species Difference of the Hepatotoxicity of Medicine Based on Transcriptome - Xu, Ziying; Kang, Qianjun; Yu, Zihui; Tian, Lichun; Zhang, Jingxuan; Wang, Ting (Frontiers in Pharmacology, 2021)
In recent years, many drugs have been withdrawn from the market by drug oversight agencies due to hepatotoxicity, which makes the research of drug induced liver injury (DILI) more and more concerned. Most of the research on DILI tend to choose rats or mice as animal model for drug toxicity detection, but the toxicities of the same kind of drugs are often different in rats or mice. Such inconsistency of animal experiment results from different species of animals will affect the extrapolation of experimental results in human. So, it is particularly important to choose the most suitable animal model for drug hepatotoxicity research because there are great differences in genome through the evolution between rats and mice. In our research, genome wide transcriptome analysis was used to explore the liver toxicity caused by species difference. It will provide the preclinical basis for the research of drug hepatotoxicity mechanism and the selection of animal models for safety evaluation. The common rat and mice models (Sprague-Dawley rat and Wistar rat, ICR mice and Kunming mice) were used and by transcriptome sequencing, with the differentially expressed genes in rat and mouse livers as the entry point, we deeply explored the mechanism of oxidative stress and the difference of gene expression in fat metabolism pathway between rats and mice. Meanwhile, the clinical identified hepatotoxic drugs, fructus psoraleae and acetaminophen were used for validation, though pathology we confirmed that oxidative stress in mice is more serious than that in rats, and KM mice were more suitable for the study of oxidative stress-related drug induced liver injury. and the reliability of the results was further verified by gene expression. Our study will provide reference for the preclinical potential hepatotoxicity evaluation, prediction and early diagnosis of drug-induced liver injury caused by traditional Chinese medicine or Chemical drugs, and provide relevant research ideas for drug toxicity research.